Para que servem os comentários de leitores na internet? : estudo sobre a utilidade da ferramenta nos sites de notícias a partir da estrutura do dispositivo e do modo de apropriação do internauta e do veículo - Bueno, Thaisa Cristina (2015)
The purpose of this thesis is trying to understand the use of the tool “readers‟ comments” on national news sites having as its starting point the device structure, the way the internet user appropriates it, and finally, how the media organization gives meaning to the material available there. The study is based on theoretical assumptions of the Medium Theory and Symbolic Interactionism, and make use of mapping as a tool of data gathering. The selection of media organizations analyzed took into account the platforms present in four categories of journalistic products, selecting among the five most widely read of each of them in the Brazilian media - portals, cyberjournals, monthly and weekly magazines - and makes a comparison between devices that mediate or not posts from readers. The result points to some divergent interests that make the relationship between what the Internet users search and what media organization authorizes the reader to do, and also the ignorance, in many cases, on how to exploit the potential of the tool by those involved in the process.